Influence of the Host and Parasite Strain on the Immune Response During Toxoplasma Infection - Mukhopadhyay, Debanjan; Arranz-Solís, David; Saeij, Jeroen P. J. (Frontiers in Cellular and Infection Microbiology, 2020)
Toxoplasma gondii is an exceptionally successful parasite that infects a very broad host range, including humans, across the globe. The outcome of infection differs remarkably between hosts, ranging from acute death to sterile infection. These differential disease patterns are strongly influenced by both host- and parasite-specific genetic factors. In this review, we discuss how the clinical outcome of toxoplasmosis varies between hosts and the role of different immune genes and parasite virulence factors, with a special emphasis on Toxoplasma-induced ileitis and encephalitis.